Zapożyczenia greckie i łacińskie a polsko-rosyjskie kontakty językowe - Behrendt, Sonia (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2013)
The article presents an analysis of 140 random lexemes of Greek and Latin origin excerpted from Słownik kieszonkowy polsko-rosyjski i rosyjsko-polski [Pocket Polish-Russian and Russian-Polish Dictionary] edited by I. Mitronova, G. Sinicyna and G. Lipkes. The corpus is, according to lexicographers and linguists, an effect of mutual influences of Polish and Russian languages. The opinions on origins of words differ among researchers, and the article attempts to verify the previously accepted judgements by M. Vasmer, W. Witkowski and Z. Rysiewicz, based on informations included in monographs by D. Moszyńska, H. Leeming, S. Kochman, and in historical dictionaries of both languages. With reference to almost 75% of the analysed material, the direction of loanword acquisition proposed by Vasmer, Witkowski and Rysiewicz has been confirmed. However, for about a quarter of the random sample of words, the accepted opinion is not confirmed by more recent historical dictionaries, nor by the lexical material provided in the monographs. The article proposes new results for the direction of loanword migration in this group of vocabulary.